Hard carbon and its manufacturing method, secondary battery and power consumption device containing the same

A tailored manufacturing process for hard carbon addresses capacity and efficiency limitations by optimizing structural properties, resulting in improved performance for secondary batteries.

JP7603814B2Active Publication Date: 2024-12-20CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023531034
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2024-12-20
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

Existing hard carbon materials for secondary batteries have limitations in capacity, initial coulombic efficiency, and rate characteristics, failing to meet the demands for high energy density and long service life.

Method used

A manufacturing method involving low-temperature heat treatment in an inert atmosphere, followed by a secondary low-temperature heat treatment in an air atmosphere, and a high-temperature carbonization process in an inert atmosphere, to produce hard carbon with specific nitrogen adsorption characteristics, particle size, and structural properties that enhance capacity and initial coulombic efficiency.

Benefits of technology

The produced hard carbon achieves higher capacity, initial coulombic efficiency, and improved rate characteristics, suitable for secondary batteries requiring enhanced energy density and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603814000003
    Figure 0007603814000003
  • Figure 0007603814000004
    Figure 0007603814000004
  • Figure 0007603814000005
    Figure 0007603814000005
Patent Text Reader

Abstract

In this application, the nitrogen adsorption isotherm measured at a temperature of 77 K shows that the nitrogen relative pressure P / P0 is 10 -8 The total amount of nitrogen adsorption between Vcm and 0.035 3 (STP) / g, and the total nitrogen adsorption amount between the nitrogen relative pressure P / P0 of 0.035 and 1 is V2cm 3 (STP) / g, V2 / V1≦0.20 and 20≦V1≦150, where P represents the absolute pressure of nitrogen and P0 represents the saturated vapor pressure of nitrogen at a temperature of 77 K, and a method for producing the same, as well as a secondary battery and a power consuming device containing the same, are provided. The present application can simultaneously improve the capacity and initial coulombic efficiency of the hard carbon.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of battery technology, and more particularly to hard carbon and a method for producing the same, as well as a secondary battery and a power consuming device containing the same. [Background technology]

[0002] In recent years, secondary batteries have been widely applied in energy storage power systems such as hydroelectric, thermal, wind and solar power plants, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. With the application and popularity of secondary batteries, their energy density, service life and rate characteristics have attracted more and more attention. Graphite is the most common negative electrode active material in secondary batteries, but its theoretical capacity is only 372 mAh / g, leaving very limited room for improving energy density, and graphite has a small interlayer distance, which limits the improvement of rate characteristics. Hard carbon, as a new negative electrode active material, can realize rapid insertion and desorption of active ions during the charge and discharge process of secondary batteries, and has great potential for development. However, hard carbon has low capacity and initial Coulombic efficiency, which limits the improvement of the energy density, service life and rate characteristics of secondary batteries. Summary of the Invention

[0003] An object of the present application is to provide a hard carbon intended to simultaneously improve the capacity and initial coulombic efficiency of the hard carbon, a method for producing the same, and a secondary battery and power consuming device containing the same.

[0004] In the first aspect of the present application, in the nitrogen adsorption isotherm measured at a temperature of 77K, the nitrogen relative pressure P / P0 is 10 -8 The total amount of nitrogen adsorption between Vcm and 0.035 3 (STP) / g, and the total nitrogen adsorption amount between the nitrogen relative pressure P / P0 of 0.035 and 1 is V2cm 3(STP) / g, V2 / V1≦0.20, and 20≦V1≦150, where P represents the absolute pressure of nitrogen, and P0 represents the saturated vapor pressure of nitrogen at a temperature of 77K.

[0005] Compared with currently commercialized hard carbons, the hard carbons provided by the present application have both high capacity and initial coulombic efficiency. Although the mechanism is not yet clear, the inventors speculate that one possible reason is that the hard carbons of the present application have an appropriate number of defects and a unique channel structure, which provides many storage sites for active ions and a high utilization rate, and therefore the hard carbon structure of the present application can easily insert, store, and desorb active ions, thereby enabling the hard carbons of the present application to achieve both high capacity and initial coulombic efficiency.

[0006] In any embodiment of the present application, 50≦V1≦150. Preferably, 70≦V1≦150. When V1 is within an appropriate range, the hard carbon provided by the present application can have both higher capacity and initial coulombic efficiency.

[0007] In any embodiment of the present application, 0.05≦V2 / V1≦0.20. Preferably, 0.08≦V2 / V1≦0.20. When V2 / V1 is within a suitable range, the hard carbon has both higher capacity and higher initial coulombic efficiency.

[0008] In any embodiment of the present application, 4≦V2≦30. Preferably, 6≦V2≦30. When V2 is within an appropriate range, the hard carbon has both higher capacity and higher initial coulombic efficiency, and at the same time has excellent rate characteristics.

[0009] In any embodiment of the present application, in the Raman spectrum of the hard carbon, I d / I g is 1.20 to 1.32, and I d is 1350±50cm -1represents the d-band peak intensity in the Raman shift range of I g is 1580±50cm -1 At this time, the degree of order in the hard carbon structure is appropriate, so that the hard carbon has both higher capacity and higher initial coulombic efficiency, and further has better rate characteristics.

[0010] In any embodiment of the present application, in the X-ray diffraction spectrum of the hard carbon, the 2θ value corresponding to the 002 peak is between 22° and 24°.

[0011] In any embodiment of the present application, the hard carbon has a volume particle size Dv50 of 2 μm to 15 μm, and preferably 4 μm to 8 μm.

[0012] In any embodiment of the present application, the hard carbon has a volume particle size Dv90 of 5 μm to 25 μm, and preferably 8 μm to 15 μm.

[0013] When the volume particle size Dv50 and / or Dv90 of the hard carbon is within an appropriate range, it is advantageous to improve the transport properties of active ions and electrons, thereby further improving the rate characteristics of the secondary battery.

[0014] In any embodiment of the present application, the specific surface area of ​​the hard carbon is 5 m 2 / g or less, preferably 0.5m 2 / g~5m 2 / g. When the specific surface area of ​​the hard carbon is within a suitable range, the hard carbon can have both higher capacity and higher initial coulombic efficiency, and also has better rate characteristics. In addition, when the specific surface area of ​​the hard carbon is within a suitable range, a stronger binding force can be formed between the hard carbon and the binder, thereby improving the cohesive force and adhesive force of the negative electrode sheet, reducing the volume expansion of the negative electrode sheet during the cycle process, and the secondary battery can have better cycle characteristics.

[0015] In any embodiment of the present application, the hard carbon has a powder compaction density of 0.96 g / cm at an applied force of 50,000 N. 3 ~1.05g / cm 3 When the powder compaction degree of the hard carbon is within an appropriate range, the compaction degree of the negative electrode sheet can be increased, thereby improving the energy density of the secondary battery.

[0016] In any embodiment of the present application, the tap density of the hard carbon is 0.80 g / cm 3 ~0.95g / cm 3 When the tap density of the hard carbon is within an appropriate range, the green density of the negative electrode sheet can be increased, thereby improving the energy density of the secondary battery.

[0017] A second aspect of the present application includes a step S10 of providing a carbon source, a step S20 of heat-treating the carbon source in an inert atmosphere at a first temperature T1 for a time t1 to obtain a first intermediate product, a step S30 of heat-treating the obtained first intermediate product in an air atmosphere at a second temperature T2 for a time t2 to obtain a second intermediate product, and a step S40 of carbonizing the obtained second intermediate product in an inert atmosphere at a third temperature T3 for a time t3 to obtain hard carbon, wherein the hard carbon has a nitrogen relative pressure P / P0 of 10 -8 The total amount of nitrogen adsorption between Vcm and 0.035 3 (STP) / g, and the total nitrogen adsorption amount between the nitrogen relative pressure P / P0 of 0.035 and 1 is V2cm 3 (STP) / g, V2 / V1≦0.20, and 20≦V1≦150, where P represents the absolute pressure of nitrogen, and P0 represents the saturated vapor pressure of nitrogen at a temperature of 77K.

[0018] The inventors have discovered that by simultaneously performing a low-temperature heat treatment process in an inert atmosphere, a secondary low-temperature heat treatment process in an air atmosphere, and a high-temperature carbonization process in an inert atmosphere on the carbon source, the obtained hard carbon can have both high capacity and high initial Coulomb efficiency. The method for manufacturing hard carbon provided in this application is simple and suitable for commercial production.

[0019] In any embodiment of this application, T1 < T3 and T2 < T3.

[0020] In any embodiment of this application, T1 ≤ T2, and preferably, T1 < T2.

[0021] In any embodiment of this application, T1 ≤ 300 °C, and preferably, T1 is 180 °C to 300 °C. When T1 is within an appropriate range, it is suitable for introducing an appropriate channel structure and can retain a large number of stable and non-collapsible skeletal structures.

[0022] In any embodiment of this application, T2 < 400 °C, and preferably, T2 is 270 °C to 380 °C. When T2 is within an appropriate range, the carbon skeletal material particles obtained in step S20 can form an appropriate and abundant channel structure from the inside to the outside, improving the transport performance of active ions and electrons, thereby improving the capacity and initial Coulomb efficiency of hard carbon.

[0023] In any embodiment of this application, T3 is 1000 °C to 1600 °C, and preferably, T3 is 1000 °C to 1400 °C. When T3 is within an appropriate range, the degree of order of hard carbon can be improved more favorably, and the hard carbon can have both high capacity and high initial Coulomb efficiency.

[0024] In any embodiment of this application, t1 is 4 h to 60 h.

[0025] In any embodiment of the present application, t2 is 1h to 12h.

[0026] In any embodiment of the present application, t3 is 1h to 12h.

[0027] In any embodiment of the present application, after step S20 and before step S30, the manufacturing method further includes step S21, which crushes the first intermediate product obtained in step S20 to ensure that the first intermediate product can be sufficiently in contact with air during subsequent processing.

[0028] In any embodiment of the present application, after step S30 and before step S40, the manufacturing method further includes step S31 of crushing the second intermediate product obtained in step S30. Preferably, the volume particle size of the second intermediate product after crushing satisfies the requirement that Dv50 is 2 μm to 15 μm and / or Dv90 is 5 μm to 25 μm.

[0029] In any embodiment of the present application, the manufacturing method further includes step S50 of crushing the hard carbon obtained in step S40 to meet the required particle size requirements and facilitate the manufacturing of the negative electrode paste and the negative electrode sheet.

[0030] In any embodiment of the present application, the inert atmosphere is selected from one or more of a nitrogen atmosphere and an argon atmosphere.

[0031] In any embodiment of the present application, the carbon source comprises one or more of a polymer, a resin, and a biomass material.

[0032] In any embodiment of the present application, the polymer comprises one or more of polyaniline, polypyrrole.

[0033] In any embodiment of the present application, the resin comprises one or more of a phenolic resin, an epoxy resin.

[0034] In any embodiment of the present application, the biomass material comprises one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, and preferably the starch comprises one or more of cereal starch, potato starch, and legume starch.

[0035] A third aspect of the present application provides a secondary battery including a negative electrode sheet comprising the hard carbon according to the first aspect of the present application or the hard carbon produced by the method according to the second aspect of the present application.

[0036] A fourth aspect of the present application provides a power consumption device including a secondary battery according to the third aspect of the present application.

[0037] The power consuming device of the present application includes the secondary battery provided by the present application, and therefore has at least the same advantages as said secondary battery. [Brief description of the drawings]

[0038] In order to more clearly describe the technical solutions in the embodiments of the present application, the following briefly describes the drawings required in the embodiments of the present application. It should be understood that the drawings shown below are only some embodiments of the present application, and those skilled in the art can further obtain other drawings based on the drawings without creative efforts.

[0039] [Figure 1] Six common adsorption isotherm types for solid materials are shown. [Diagram 2] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 3] 3 is an exploded schematic view of the secondary battery shown in FIG. 2 according to the embodiment. FIG. [Figure 4] FIG. 1 is a schematic diagram of an embodiment of a battery module of the present application. [Diagram 5] FIG. 1 is a schematic diagram of an embodiment of a battery pack of the present application. [Figure 6] 6 is an exploded schematic view of the battery pack shown in FIG. 5 according to the embodiment. [Figure 7]1 is a schematic diagram of an embodiment of a power consuming device including a secondary battery of the present application as a power source. [Figure 8] 2 is a scanning electron microscope (SEM) photograph of the hard carbon produced in Example 2. [Figure 9] 2 is a nitrogen adsorption isotherm measured at a temperature of 77 K of the hard carbon produced in Example 2. [Figure 10] 2 is a nitrogen adsorption isotherm measured at a temperature of 77K for the hard carbon produced in Comparative Example 1.

[0040] In the drawings, the drawings are not drawn to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] Hereinafter, the embodiments specifically disclosing the hard carbon of the present application, its manufacturing method, and the secondary battery and power consumption device containing the same will be described in detail with reference to the drawings as appropriate. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and overlapping description of substantially the same structure may be omitted. This is to prevent the following description from becoming unnecessarily redundant and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0042] The "ranges" disclosed herein are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner may or may not include the endpoints and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are recited for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. Also, if minimum range values ​​1 and 2 are recited, and maximum range values ​​3, 4, and 5 are recited, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all contemplated. In this application, unless otherwise stated, the numerical range "a-b" means a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are fully recited herein, and "0-5" is merely a shorthand for combinations of these numerical values. Additionally, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0043] All embodiments and optional embodiments of the present application, unless otherwise specified, can be combined with each other to form new technical solutions, and such technical solutions should be considered as included in the disclosure of the present application.

[0044] All technical features and optional technical features of the present application, unless otherwise specified, can be combined with each other to form new technical solutions, and such technical solutions should be considered as included in the disclosure of the present application.

[0045] All steps in this application can be performed in sequence or randomly, and are preferably performed in sequence, unless otherwise stated. For example, when the method includes steps (a) and (b), it indicates that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, when the method described may further include step (c), it indicates that step (c) may be added to the method in any order, such as the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0046] The terms "comprise" and "comprises" referred to in this application refer to both open and closed formats unless otherwise specified. For example, the terms "comprise" and "comprises" can indicate that other components not listed may also be included or may include, or that only the listed components may be included or may include.

[0047] In this application, unless otherwise stated, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied by either A being true (or present) and B being false (or absent), or A being false (or absent) and B being true (or present), or both A and B being true (or present).

[0048] In this application, unless otherwise specified, the term "active ion" means an ion that can be inserted and removed back and forth between the positive electrode and the negative electrode of a secondary battery, and includes, but is not limited to, lithium ions, sodium ions, and the like.

[0049] According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), micropores refer to pores with a pore diameter of <2 nm, mesopores refer to pores with a pore diameter of 2 nm to 50 nm, and macropores refer to pores with a pore diameter of >50 nm. In the context of this application, the term "micropores" refers to pores with a pore diameter of <2 nm, the term "mesopores" refers to pores with a pore diameter of 2 nm to 50 nm, and the term "macropores" refers to pores with a pore diameter of >50 nm. In the context of this application, the terms "larger pores" and "smaller pores" are relative concepts.

[0050] A secondary battery, also called a rechargeable battery or storage battery, is a battery that can continue to be used by activating the active material by charging after the battery is discharged. Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the charging and discharging process of the battery, active ions are inserted and removed by going back and forth between the positive electrode sheet and the negative electrode sheet. The separator is installed between the positive electrode sheet and the negative electrode sheet, and mainly serves to prevent short circuit between the positive and negative electrodes, while allowing the active ions to pass through. The electrolyte serves to conduct the active ions between the positive electrode sheet and the negative electrode sheet. At present, secondary batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind, and solar power plants, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace.

[0051] With the application and popularity of secondary batteries, their energy density, service life and rate characteristics have been attracting more and more attention. The characteristics of the negative electrode active material can determine the energy density, service life and safety of the secondary battery to a certain extent. Graphite (including natural graphite and synthetic graphite) is the most common negative electrode active material in secondary batteries, but its theoretical capacity is only 372mAh / g, and there is very limited room for improving the energy density. In addition, graphite has a small interlayer distance, which limits the improvement of the rate characteristics and cannot meet the actual needs of secondary batteries for high rate characteristics.

[0052] Hard carbon is carbon that is difficult to graphitize, and is difficult to graphitize even at high temperatures of 2500°C or higher. Hard carbon is a carbon material with a complex structure and a graphite microcrystalline structure, where the graphite crystallites are irregularly arranged, the number of graphite microcrystalline layer sheets is small, and the edge faces of the layers may be bridged. The structure of hard carbon also includes amorphous regions, which mainly include pores, defects, sp3 hybridized carbon atoms, carbon chains, some functional groups, etc. Therefore, there may be multiple active ion storage sites in the structure of hard carbon, such as the surface of graphite microcrystals, between graphite microcrystal layers, the edge faces and pores of graphite microcrystalline layer sheets, etc.

[0053] Compared with graphite, the spacing of the hard carbon layers is larger and the pore structure is more abundant, which is therefore favorable for the storage, rapid insertion and desorption of active ions, so that the secondary battery can have excellent low-temperature characteristics, output characteristics and safety, and hard carbon has unique advantages, especially in the field of power batteries. However, most of the hard carbons currently on the market belong to low-capacity common hard carbons, and have low capacity and initial coulombic efficiency, for example, the capacity is generally between 200mAh / g and 280mAh / g, and the initial coulombic efficiency is generally less than 80%, which is quite limited in practical applications.

[0054] Therefore, how to simultaneously improve the capacity and initial coulombic efficiency of hard carbon remains a technical problem that needs to be urgently solved.

[0055] In view of this, a first aspect of an embodiment of the present application provides a hard carbon that can achieve both high capacity and initial coulombic efficiency, and can provide a secondary battery with high energy density, long service life, and excellent rate characteristics.

[0056] In the hard carbon according to the first aspect of the present invention, the nitrogen relative pressure P / P0 is 10 -8 The total amount of nitrogen adsorption between Vcm and 0.035 3(STP) / g, and the total nitrogen adsorption amount between the nitrogen relative pressure P / P0 of 0.035 and 1 is V2cm 3 (STP) / g, V2 / V1≦0.20, and 20≦V1≦150 are satisfied, P represents the absolute pressure of nitrogen, and P0 represents the saturated vapor pressure of nitrogen at a temperature of 77K.

[0057] The K above is the unit of absolute temperature, Kelvin, and 77K indicates the temperature of liquid nitrogen.

[0058] When gas molecules move to the surface of a solid material, due to the interaction between the gas molecules and the surface molecules of the solid material (e.g., van der Waals forces or chemical bonds, etc.), the gas molecules temporarily remain on the surface of the solid, increasing the concentration of the gas molecules on the surface of the solid material, and such a phenomenon is called the adsorption of gas molecules on the surface of the solid material. The gas can be called the adsorbate, and the solid material can be called the adsorbent. The adsorption isotherm is the relationship curve between the concentrations of the adsorbate in two phases when the adsorption process of the adsorbate (e.g., gas) proceeding at the interface between two phases (e.g., the interface between a gas and a solid material) at a certain temperature reaches equilibrium. The channel structure of solid materials is different, and the types of adsorption isotherms are also different. Figure 1 shows six common types of adsorption isotherms of solid materials.

[0059] The hard carbon of the present invention has a nitrogen adsorption isotherm measured at a temperature of 77 K, and the nitrogen relative pressure P / P0 is 10 -8 Total nitrogen adsorption V1cm between 0.035 and 0.035 3 (STP) / g and the total nitrogen adsorption amount V2cm when the nitrogen relative pressure P / P0 is between 0.035 and 1 3 (STP) / g satisfies the requirement of V2 / V1≦0.20, therefore, the adsorption process of the hard carbon of the present invention is mainly in the stage where the relative pressure is low, i.e., P / P0 is 10 -8 At the same time, the hard carbon of the present invention is generated at a stage where the nitrogen relative pressure P / P0 is between 10 -8 When the total amount of nitrogen adsorption V1 is 0.035, 3 (STP) / g to 150cm 3 (STP) / g.

[0060] Compared with currently commercialized hard carbons, the hard carbons provided by the present application have both high capacity and initial coulombic efficiency. Although the mechanism is not yet clear, the inventors speculate that one possible reason is that the hard carbons of the present application have an appropriate number of defects and a unique channel structure, which provides many storage sites for active ions and a high utilization rate, and therefore the hard carbon structure of the present application can easily insert, store, and desorb active ions, thereby enabling the hard carbons of the present application to achieve both high capacity and initial coulombic efficiency.

[0061] Currently, commercial hard carbon has a nitrogen adsorption isotherm measured at a temperature of 77 K with a nitrogen relative pressure P / P0 of 10 -8 Total nitrogen adsorption V1cm between 0.035 and 0.035 3 (STP) / g and the total nitrogen adsorption amount V2cm when the nitrogen relative pressure P / P0 is between 0.035 and 1 3 (STP) / g do not meet the requirement of V2 / V1≦0.20. The possible reasons are that the commercialized hard carbon has many internal defects, unreasonable channel structure or few micropore structure, which cannot provide many active ion storage sites, and the utilization rate of the only active ion storage site is low. In addition, the commercialized hard carbon may contain a high content of mesopore or macropore structure, which increases the proportion of electrolyte infiltration area inside the hard carbon. After further research, the inventors found that the higher the ratio of V2 to V1 in the adsorption isotherm, the higher the proportion of electrolyte infiltration area inside the hard carbon, which leads to a higher initial irreversible capacity loss of the hard carbon and a lower initial coulombic efficiency.

[0062] In addition, the nitrogen relative pressure P / P0 of hard carbon is 10 -8 The total amount of nitrogen adsorbed when the concentration is 0.035 is 20 cm 3If it is less than (STP) / g, the channel structure of the hard carbon is not developed and the specific surface area is too low, so that the hard carbon cannot provide many active ion storage sites, and therefore the specific capacity of the hard carbon is low. At the same time, the channel structure of the hard carbon is not developed, so that the active ions stored in the storage sites are not easily desorbed, and therefore the initial Coulombic efficiency of the hard carbon is also low.

[0063] Hard carbon nitrogen relative pressure P / P0 is 10 -8 The total amount of nitrogen adsorption at 0.035 is 150 cm 3 If the hard carbon exceeds (STP) / g, the hard carbon structure becomes brittle, which causes the internal channel structure to collapse and the pores to merge, and the proportion of mesopores or macropores in the hard carbon becomes too high, which easily causes a large amount of electrolyte to penetrate. Therefore, although hard carbon can provide many active ion storage sites and a high specific capacity, the structure of the hard carbon is too complex, making it impossible for some active ions stored in the active ion storage sites to be desorbed, resulting in a decrease in the initial coulombic efficiency of the hard carbon.

[0064] The hard carbon provided by this application has a nitrogen relative pressure P / P0 of 10 -8 Total nitrogen adsorption V1cm between 0.035 and 0.035 3(STP) / g satisfies the requirement of 20≦V1≦150. The larger V1 is, the more active ion storage sites the hard carbon provides, and the larger the capacity of the hard carbon is. In some embodiments, it is preferable that V1 is 30≦V1≦150, 40≦V1≦150, 50≦V1≦150, 60≦V1≦150, 70≦V1≦150, 80≦V1≦150, 90≦V1≦150, 100≦V1≦150, 110≦V1≦150, 120≦V1≦150, 30≦V1≦140, 40≦V1≦140, 50≦V1≦140, 60≦V1≦140, 70≦V1≦140, 80≦V1≦140, 90≦V1≦140, 100≦V1≦140, 110 ≦V1≦140, 120≦V1≦140, 30≦V1≦130, 40≦V1≦130, 50≦V1≦130, 60≦V1≦130, 70≦V1≦130, 80≦V1≦130, 90≦V1≦130, 100≦V1≦130, 110≦V1≦130, 30≦V1≦120, 40≦V1≦120, 50≦V1≦120, 60≦V1≦120, 70≦V1≦120, 80≦V1≦120, 90≦V1≦120, 100≦V1≦120, 110≦V1≦120. When V1 is within an appropriate range, the hard carbon provided by the present application can have both higher capacity and initial coulombic efficiency.

[0065] The hard carbon provided by this application is a material having a nitrogen relative pressure P / P0 of 10 -8 Total nitrogen adsorption V1cm between 0.035 and 0.035 3 (STP) / g and the total nitrogen adsorption amount V2cm when the nitrogen relative pressure P / P0 is between 0.035 and 1 3(STP) / g meets the requirement of V2 / V1≦0.20. Within this range, the hard carbon can have a suitable channel structure, can provide more active ion storage sites, and has a high utilization rate of the active ion storage sites. At the same time, the channel structure inside the hard carbon is mainly micropore structure, and the content of mesopore or macropore structure is suitable, so that the electrolyte infiltration area inside the hard carbon can be reduced. In some embodiments, V2 / V1 can be ≦0.19, ≦0.18, ≦0.17, ≦0.16, ≦0.15, ≦0.14, ≦0.13, ≦0.12, ≦0.11, ≦0.10. At the same time, V2 / V1 cannot be too low, in which case the active ions stored in the active ion storage sites have high difficulty in desorption. In some embodiments, it is preferable that 0.05≦V2 / V1≦0.20, 0.06≦V2 / V1≦0.20, 0.08≦V2 / V1≦0.20, 0.10≦V2 / V1≦0.20, 0.12≦V2 / V1≦0.20, 0.14≦V2 / V1≦0.20, 0.16≦V2 / V1≦0.20, 0.05≦V2 / V1≦0.18, 0.06≦V2 / V1≦0.18, 0.08≦V2 / V1≦0.18, 0.10≦V2 / V1≦0.18, 0.12≦V2 / V1≦0.18, 0.14≦V2 / V1≦0.18, 0.16≦V2 / V1≦0.18, 0.05≦V2 / V1≦0.16, 0.06≦V2 / V1≦0.16, 0.08≦V2 / V1≦0.16, 0.10≦V2 / V1≦0.16, 0.12≦V2 / V1≦0.16, 0.14≦V2 / V1≦0.16. When V2 / V1 is within the appropriate range, hard carbon has both higher capacity and higher initial coulombic efficiency.

[0066] In some embodiments, 0 < V2 ≤ 30. When V2 is high, the proportion of the electrolyte infiltration region inside the hard carbon is high, and the loss of the initial irreversible capacity of the hard carbon increases. At the same time, V2 should not be too low. When V2 is low, it is difficult for active ions to desorb and insert quickly, and the rate performance of the hard carbon may decrease. Preferably, 1 ≤ V2 ≤ 30, 2 ≤ V2 ≤ 30, 3 ≤ V2 ≤ 30, 4 ≤ V2 ≤ 30, 5 ≤ V2 ≤ 30, 6 ≤ V2 ≤ 30, 7 ≤ V2 ≤ 30, 8 ≤ V2 ≤ 30, 9 ≤ V2 ≤ 30, 10 ≤ V2 ≤ 30, 1 ≤ V2 ≤ 25, 2 ≤ V2 ≤ 25, 3 ≤ V2 ≤ 25, 4 ≤ V2 ≤ 25, 5 ≤ V2 ≤ 25, 6 ≤ V2 ≤ 25, 7 ≤ V2 ≤ 25, 8 ≤ V2 ≤ 25, 9 ≤ V2 ≤ 25, 10 ≤ V2 ≤ 25, 1 ≤ V2 ≤ 20, 2 ≤ V2 ≤ 20, 3 ≤ V2 ≤ 20, 4 ≤ V2 ≤ 20, 5 ≤ V2 ≤ 20, 6 ≤ V2 ≤ 20, 7 ≤ V2 ≤ 20, 8 ≤ V2 ≤ 20, 9 ≤ V2 ≤ 20, 10 ≤ V2 ≤ 20. When V2 is within an appropriate range, the hard carbon has both a higher capacity and a higher initial Coulombic efficiency, and at the same time has excellent rate performance.

[0067] In some embodiments, the hard carbon simultaneously satisfies the requirements of 0.08 ≤ V2 / V1 ≤ 0.20, 70 ≤ V1 ≤ 150, and 6 ≤ V2 ≤ 30. At this time, the hard carbon can provide more active ion storage sites, thereby having a higher capacity. At the same time, the inside of the hard carbon has an appropriate channel structure, which not only facilitates the insertion and storage of active ions, but also does not inhibit the desorption of active ions, and the utilization rate of the active ion storage sites is also high. In addition, the channel structure inside the hard carbon is mainly a micropore structure, and the content of mesopore or macropore structure is appropriate, thereby reducing the electrolyte infiltration region inside the hard carbon. Therefore, the hard carbon has both a higher capacity and a higher initial Coulombic efficiency, and at the same time has excellent rate performance. In some embodiments, the hard carbon simultaneously satisfies the requirements of 0.08 ≤ V2 / V1 ≤ 0.20, 85 ≤ V1 ≤ 140, and 7 ≤ V2 ≤ 25.

[0068] In some embodiments, the Raman spectrum of the hard carbon includes I d / I g is 1.20 to 1.32, and I d is 1350±50cm - represents the d-band peak intensity in the Raman shift range of 1, and I g is 1580±50cm -1 The Raman shift range of the g-band peak intensity is shown in Fig. 1, and the laser wavelength λ is 532 nm.

[0069] The d-band peak is due to lattice defects of carbon atoms, and the g-band peak is due to the in-plane vibration of sp2 carbon atoms. In hard carbon structures, the d-band peak intensity is related to the number of defects in the hard carbon structure, and the g-band peak intensity is related to the number of graphite crystallites in the hard carbon structure, and therefore, I d / I g can characterize the degree of order in hard carbon structures. d / I g The smaller the I, the higher the degree of order in the hard carbon structure and the higher the perfection of the carbon surface, which improves the initial Coulombic efficiency of the hard carbon, but reduces the capacity and rate characteristics. d / I g is 1.20 to 1.32, and at this time, the degree of order of the hard carbon structure is appropriate, so that the hard carbon has both higher capacity and higher initial coulombic efficiency, and further has better rate characteristics.

[0070] In some embodiments, in the X-ray diffraction spectrum of the hard carbon, the 2θ value corresponding to the 002 peak is between 22° and 24°.

[0071] In some embodiments, the hard carbon has a volume particle size Dv50 of 2 μm to 15 μm, preferably 4 μm to 8 μm.

[0072] In some embodiments, the hard carbon has a volume particle size Dv90 of 5 μm to 25 μm, preferably 8 μm to 15 μm.

[0073] In some embodiments, the hard carbon simultaneously satisfies the requirements that the volume particle diameter Dv50 is 4 μm to 8 μm and the volume particle diameter Dv90 is 8 μm to 15 μm.

[0074] When the volume particle size Dv50 and / or Dv90 of the hard carbon is within an appropriate range, it is advantageous to improve the transport properties of active ions and electrons, thereby further improving the rate characteristics of the secondary battery.

[0075] In some embodiments, the specific surface area of ​​the hard carbon is 5 m 2 Preferably, the specific surface area of ​​the hard carbon is 0.1 m 2 / g~5m 2 / g, 0.5m 2 / g~5m 2 / g, 1m 2 / g~5m 2 / g, 1.5m 2 / g~5m 2 / g, 2m 2 / g~5m 2 / g, 2.5m 2 / g~5m 2 / g, 3m 2 / g~5m 2 / g, 3.5m 2 / g~5m 2 / g, 4m 2 / g~5m 2 / g, 0.5m 2 / g~4m 2 / gm 2 / g, 1m 2 / g~4m 2 / g, 1.5m 2 / g~4m 2 / g, 2m 2 / g~4m 2 / g, 2.5m 2 / g~4m 2 / g, 3m 2 / g~4m 2 / g, 0.5m2 / g~3m 2 / g, 1m 2 / g~3m 2 / g, 1.5m 2 / g~3m 2 / g, 2m 2 / g~3m 2 / g. A low specific surface area helps to reduce the surface activity of the hard carbon and reduce the formation of a solid electrolyte interphase interface (SEI film), thereby improving the initial Coulombic efficiency of the hard carbon and the secondary battery, and a higher specific surface area helps to accelerate the transport of active ions, thereby improving the rate characteristics of the secondary battery. When the specific surface area of ​​the hard carbon is within a suitable range, the hard carbon can have both higher capacity and initial Coulombic efficiency, and also has better rate characteristics. In addition, when the specific surface area of ​​the hard carbon is within a suitable range, a stronger binding force can be formed between the hard carbon and the binder, thereby improving the cohesive force and adhesive force of the negative electrode sheet, reducing the volume expansion of the negative electrode sheet during the cycle process, and the secondary battery has better cycle characteristics.

[0076] In some embodiments, the hard carbon has a green density of 0.96 g / cm at a force of 50,000 N. 3 ~1.05g / cm 3 When the green density of the hard carbon is within an appropriate range, the green density of the negative electrode sheet can be increased, thereby improving the energy density of the secondary battery.

[0077] In some embodiments, the hard carbon has a tap density of 0.80 g / cm 3 ~0.95g / cm 3 When the tap density of the hard carbon is within an appropriate range, the green density of the negative electrode sheet can be increased, thereby improving the energy density of the secondary battery.

[0078] In this application, the nitrogen gas adsorption test of hard carbon at a temperature of 77 K can be performed with reference to GB / T 21650.2-2008 "Measurement of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption methods, Part 2: Analysis of mesopores and macropores by gas adsorption method". For example, the measurement can be performed using a surface area and pore size analyzer such as ASAP 2460 type surface area and pore size analyzer manufactured by Micromeritics, USA.

[0079] In this application, the volumetric particle size Dv50 and Dv90 of hard carbon have the meanings known in the art, which indicate the particle size when the cumulative volume distribution percentage of the material reaches 50% and 90%, respectively, and can be measured using devices and methods known in the art, for example, see GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method, which can be easily measured using a laser particle size analyzer such as the Mastersizer 2000E type laser particle size analyzer manufactured by Malvern Corporation, UK.

[0080] In the present application, the specific surface area of ​​hard carbon has a meaning known in the art and can be measured using an apparatus and method known in the art. For example, the specific surface area can be measured using a test method for analyzing the specific surface area by nitrogen adsorption method with reference to GB / T 19587-2017, and calculated by BET (Brunauer Emmett Teller) method. The test for analyzing the specific surface area by nitrogen adsorption method can be performed using a surface area and pore size analyzer of ASAP 3020 type manufactured by Micromeritics, USA.

[0081] In this application, the green density of hard carbon has a meaning known in the art and can be measured using devices and methods known in the art. For example, it can be measured by an electronic pressure tester (such as UTM7305 type) with reference to the recommended standard GB / T24533-2009. An exemplary test method is to weigh 1 g of hard carbon powder and measure the density of the powder having a base area of ​​1.327 cm. 2The mixture is placed in a mold, pressurized to 5000 kg (equivalent to 50,000 N), and held for 30 seconds before releasing the pressure and holding for 10 seconds. The green density of the hard carbon under a force of 50,000 N is then recorded and calculated.

[0082] In this application, the tap density of hard carbon has a meaning known in the art and can be measured using an apparatus and method known in the art, for example, referring to GB / T 5162-2006, and can be measured using a powder tap density meter (such as Dandong Baite BT-301). Manufacturing method of hard carbon

[0083] A second aspect of the present embodiment provides a method for producing hard carbon, including the steps of: providing a carbon source (S10); heat-treating the carbon source in an inert atmosphere at a first temperature T1 for t1 hours to obtain a first intermediate product (S20); heat-treating the first intermediate product in an air atmosphere at a second temperature T2 for t2 hours to obtain a second intermediate product (S30); and carbonizing the second intermediate product in an inert atmosphere at a third temperature T3 for t3 hours to obtain hard carbon (S40). The hard carbon has a nitrogen adsorption isotherm measured at a temperature of 77 K, in which the nitrogen relative pressure P / P0 is 10 -8 The total amount of nitrogen adsorption between Vcm and 0.035 3 (STP) / g, and the total nitrogen adsorption amount between the nitrogen relative pressure P / P0 of 0.035 and 1 is V2cm 3 (STP) / g, V2 / V1≦0.20, and 20≦V1≦150 are satisfied, P represents the absolute pressure of nitrogen, and P0 represents the saturated vapor pressure of nitrogen at a temperature of 77K.

[0084] The production method according to the second aspect of the embodiment of the present application can produce the hard carbon according to any of the examples in the first aspect of the embodiment of the present application.

[0085] In some embodiments, T <T3であり、T2<T3である。

[0086] In some embodiments, T1≦T2. Preferably, T1 <T2である。

[0087] The inventors have discovered that by simultaneously carrying out a low-temperature heat treatment process in an inert atmosphere, a secondary low-temperature heat treatment process in an air atmosphere, and a high-temperature carbonization process in an inert atmosphere on the carbon source, the obtained hard carbon can have both high capacity and high initial coulombic efficiency, and that both the capacity and initial coulombic efficiency of the hard carbon obtained by the manufacturing method of the present application are significantly improved compared to conventional commercialized hard carbons.

[0088] The method for producing hard carbon provided by the present application is simple and suitable for commercial production.

[0089] The method for producing hard carbon provided by the present application does not require the addition of a conductive agent or other auxiliary agents, and the hard carbon obtained by the method for producing hard carbon provided by the present application has a lower heteroatom content and can further reduce the irreversible consumption of heteroatoms by active ions.

[0090] In the method for producing hard carbon provided by the present application, a carbon source is heat-treated in an inert atmosphere at a low first temperature, which can better stabilize the framework structure of the carbon source and provide a stable carbon skeleton structure for the pore formation process by the subsequent second low-temperature heat treatment and high-temperature carbonization treatment. The first intermediate product is heat-treated in an air atmosphere at a low second temperature, which can form a suitable channel structure in the carbon skeleton structure, which can facilitate the secondary pore formation process by the subsequent high-temperature carbonization treatment. The second intermediate product is heat-treated in an inert atmosphere at a high third temperature, which can improve the degree of order of the obtained hard carbon.

[0091] The type of inert atmosphere is not particularly limited, and in some embodiments, the inert atmosphere is selected from one or more of a nitrogen gas atmosphere and an argon gas atmosphere.

[0092] In some embodiments, the first temperature T1 is 300° C. or less. If the first temperature T1 is high, the skeletal structure formed after the heat treatment of the carbon source and suitable for conversion to a suitable channel structure is likely to decompose in large quantities, resulting in a lack of a suitable skeletal structure for forming a channel structure in the subsequent heat treatment process, and V1 and V2 are both small in the nitrogen adsorption isotherm measured at a temperature of 77 K of the hard carbon, resulting in a decrease in the capacity of the hard carbon. Furthermore, it is also undesirable that the first temperature T1 is too low. If the first temperature T1 is low, the degree of crosslinking after the heat treatment of the carbon source is low, the formed skeletal structure is brittle and has low stability, and when the channel structure is introduced by low-temperature heat treatment in an air atmosphere, the brittle skeletal structure is likely to collapse and the channel structure of the hard carbon is likely to decrease, resulting in a decrease in V1 shown in the nitrogen adsorption isotherm measured at a temperature of 77 K of the hard carbon. At the same time, the collapse of the skeletal structure causes the pores to merge, and the number and proportion of large-sized pores increase, further decreasing the capacity and initial coulombic efficiency of the hard carbon.

[0093] In some embodiments, the first temperature T1 may be 180° C. to 300° C., 200° C. to 300° C., 220° C. to 300° C., 240° C. to 300° C., 260° C. to 300° C., 280° C. to 300° C., 180° C. to 280° C., 200° C. to 280° C., 220° C. to 280° C., 240° C. to 280° C., 260° C. to 280° C., 180° C. to 260° C., 200° C. to 260° C., 220° C. to 260° C., 240° C. to 260° C., 180° C. to 240° C., 200° C. to 240° C., 220° C. to 240° C., or 180° C. to 220° C. When the first temperature T1 is within a suitable range, it is suitable for introducing a suitable channel structure, and can retain many stable and not easily collapsed skeletal structures.

[0094] In some embodiments, the heat treatment time t1 is 4h to 60h. Those skilled in the art can select an appropriate heat treatment time within the above range according to the first temperature used, for example, when the first temperature is high, the heat treatment time can be appropriately shortened. The heat treatment time also varies somewhat depending on the type of carbon source, and those skilled in the art can adjust it according to the actual situation.

[0095] In some embodiments, the second temperature T2 is less than 400° C. If the second temperature T2 is too high, the reaction rate between the carbon skeleton material obtained in step S20 and air is fast, and the air does not diffuse sufficiently into the interior of the material particles, so that the channel structure formed in the pore formation process is unevenly concentrated in the surface region of the particles. In addition, the channel structure after excessive pore formation in the particle surface region is easily collapsed and pores merge, and the number and proportion of large pores increase, so that both the capacity and initial Coulombic efficiency of the hard carbon are reduced. In addition, it is also undesirable that the second temperature T2 is too low. If the second temperature T2 is low, the reaction rate between the carbon skeleton material obtained in step S20 and air is slow, and the pore formation effect is weak, so that the capacity of the hard carbon is reduced.

[0096] In some embodiments, the second temperature T2 is 200°C to 395°C, 220°C to 395°C, 240°C to 395°C, 260°C to 395°C, 280°C to 395°C, 300°C to 395°C, 320°C to 395°C, 340°C to 395°C, 360°C to 395°C, 200°C to 380°C, 220°C to 380°C, 2 40℃~380℃, 260℃~380℃, 270℃~350℃, 270℃~380℃, 280℃~380℃, 300℃~380℃, 320℃~380℃, 340℃~380℃, 360℃~380℃, 290℃~380℃, 290℃~350℃, 200℃~360℃, 220℃~360℃, 240 ℃~360℃, 260℃~360℃, 280℃~360℃, 300℃~360℃, 320℃~360℃, 200℃~340℃, 220℃~340℃, 240℃~340℃, 260℃~340℃, 280℃~340℃, 300℃~340℃, 200℃~320℃, 220℃~320℃, 240℃~ The second temperature T2 may be 320°C, 260°C to 320°C, 280°C to 320°C, 200°C to 300°C, 220°C to 300°C, 240°C to 300°C, 260°C to 300°C, 200°C to 280°C, 220°C to 280°C, 240°C to 280°C, 200°C to 260°C, 220°C to 260°C, or 200°C to 240°C. When the second temperature T2 is within a suitable range, the carbon skeleton material particles obtained in step S20 can form a suitable and abundant channel structure from the inside to the outside, which improves the transport performance of active ions and electrons, thereby further improving the capacity and initial Coulombic efficiency of the hard carbon.

[0097] In some embodiments, the heat treatment time t2 is 1h to 12h. Those skilled in the art can select an appropriate heat treatment time within the above range according to the second temperature used, for example, when the second temperature is high, the heat treatment time can be appropriately shortened. The heat treatment time also varies somewhat depending on the type of carbon source, and those skilled in the art can adjust it according to the actual situation.

[0098] In some embodiments, it is preferable that if T2≦270° C., then t2≧10 h, and further, if 200° C.≦T2≦270° C., then 10 h≦t2≦12 h.

[0099] In some embodiments, preferably, when 270 °C < T2 < 400 °C, t2 ≤ 8 h, and further, when 270 °C < T2 < 400 °C, 1 h ≤ t2 ≤ 8 h

[0100] In some embodiments, 270 °C ≤ T2 ≤ 380 °C and 1 h ≤ t2 ≤ 4 h. When both meet the requirements within the above range, the capacity and initial Coulomb efficiency of the hard carbon can be further improved.

[0101] In some embodiments, the third temperature T3 is 1000 °C to 1600 °C. When the third temperature T3 is low, a large number of extremely fine pore structures in the second intermediate product structure obtained in step S30 remain, but these extremely fine pore structures have low strength and are extremely easily destroyed in the subsequent charge-discharge process, reducing the utilization rate of the active ion storage sites, thereby reducing both the capacity and the initial Coulomb efficiency of the hard carbon. Furthermore, it is not preferable if the third temperature T3 is too low. When the third temperature T3 is high, fine movement is likely to occur in the graphite microcrystalline structure formed in the carbonization treatment process, and the formed channel structure is forced to be adjusted, thereby significantly reducing the channel structure and reducing the capacity of the hard carbon.

[0102] In some embodiments, the third temperature T3 is 1100 °C to 1600 °C, 1200 °C to 1600 °C, 1300 °C to 1600 °C, 1400 °C to 1600 °C, 1500 °C to 1600 °C, 1000 °C to 1500 °C, 1100 °C to 1500 °C, 1200 °C to 1500 °C, 1300 °C to 1500 °C, 1400 °C to 1500 °C, 1000 °C to 1400 °C, 1100 °C to 1400 °C, 1200 °C to 1400 °C, 1300 °C to 1400 °C, 1000 °C to 1300 °C, 1000 °C to 1350 °C, 1100 °C to 1300 °C, 1200 °C to 1300 °C, 1000 °C to 1200 °C, 1100 °C to 1200 °C, 1000 °C to 1100 °C. When the third temperature T3 is within an appropriate range, the degree of order of the hard carbon can be improved better, and the hard carbon will have both high capacity and high initial Coulomb efficiency.

[0103] In some embodiments, the heat treatment time t3 is 1h to 12h. Those skilled in the art can select an appropriate heat treatment time within the above range according to the third temperature used, for example, when the third temperature is high, the heat treatment time can be appropriately shortened. The heat treatment time also varies somewhat depending on the type of carbon source, and those skilled in the art can adjust it according to the actual situation.

[0104] In some embodiments, the heating rate in step S20 may be 1°C / min to 10°C / min. However, the present application is not limited thereto, and the heating rate can be adjusted according to the actual situation. For example, the heating rate is 1°C / min to 9°C / min, 1°C / min to 8°C / min, 1°C / min to 7°C / min, 1°C / min to 6°C / min, 1°C / min to 5°C / min, 1°C / min to 4°C / min, 1°C / min to 3°C / min, 1°C / min to 2°C / min, 2°C / min to 10°C / min, 3°C / min to 9°C / min, 4°C / min to 8°C / min, and 5°C / min to 7°C / min.

[0105] In some embodiments, the heating rate in step S30 may be 1° C. / min to 5° C. / min. However, the present application is not limited thereto, and the heating rate can be adjusted according to the actual situation. For example, the heating rate is 1° C. / min to 4° C. / min, 1° C. / min to 3° C. / min, 1° C. / min to 2° C. / min, 2° C. / min to 5° C. / min, 2° C. / min to 4° C. / min, 2° C. / min to 3° C. / min, 3° C. / min to 5° C. / min, 3° C. / min to 4° C. / min, or 4° C. / min to 5° C. / min.

[0106] In some embodiments, the heating rate in step S40 is 1°C / min to 10°C / min. However, the present application is not limited thereto, and the heating rate can be adjusted according to the actual situation. For example, the heating rate is 1°C / min to 9°C / min, 1°C / min to 8°C / min, 1°C / min to 7°C / min, 1°C / min to 6°C / min, 1°C / min to 5°C / min, 1°C / min to 4°C / min, 1°C / min to 3°C / min, 1°C / min to 2°C / min, 2°C / min to 10°C / min, 3°C / min to 9°C / min, 4°C / min to 8°C / min, and 5°C / min to 7°C / min.

[0107] In some embodiments, after step S20 and before step S30, the manufacturing method further includes step S21 of crushing the first intermediate product obtained in step S20, for example, crushing to the order of mm, to crush the agglomerated first intermediate product at this time, and ensure that the first intermediate product can be sufficiently in contact with air during subsequent processing. Note that in some embodiments, this step may be omitted.

[0108] In some embodiments, after step S30 and before step S40, the manufacturing method further includes step S31 of crushing the second intermediate product obtained in step S30. For example, in some embodiments, the volume particle size Dv50 of the second intermediate product after crushing is 2 μm to 15 μm, preferably 4 μm to 8 μm. In some embodiments, the volume particle size Dv90 of the second intermediate product after crushing is 5 μm to 25 μm, preferably 8 μm to 15 μm. In some embodiments, the volume particle size Dv50 of the second intermediate product after crushing is 4 μm to 8 μm, and the volume particle size Dv90 is 8 μm to 15 μm. In some embodiments, the step may be omitted.

[0109] In some embodiments, the method further includes step S50 of crushing the hard carbon obtained in step S40, so that the agglomerated hard carbon is crushed to meet the required particle size requirements and facilitates the production of the negative electrode paste and the negative electrode sheet, which may be omitted in some embodiments.

[0110] The present application does not particularly limit the type of carbon source, and in some embodiments, the carbon source includes one or more of a polymer, a resin, and a biomass material.

[0111] By way of example, the polymer may include one or more of polyaniline, polypyrrole.

[0112] For example, the resin may include one or more of a phenolic resin, an epoxy resin, and preferably, the phenolic resin may include one or more of a phenol-formaldehyde resin, a resorcinol-formaldehyde resin, a hydroquinone-formaldehyde resin, and a phenol-furfural resin.

[0113] By way of example, the biomass material comprises one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin. Preferably, the starch comprises one or more of cereal starch, potato starch, legume starch. Examples of cereal starch include, but are not limited to, one or more of corn starch, rice starch, millet starch, sorghum starch, wheat starch, oat starch, buckwheat starch, rye starch, examples of potato starch include, but are not limited to, one or more of cassava starch, potato starch, sweet potato starch, yam starch, taro starch, examples of legume starch include, but are not limited to, one or more of mung bean starch, broad bean starch, pea starch, cowpea starch.

[0114] Preferably, the carbon source is selected from biomass materials. Furthermore, the carbon source is selected from one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, and lignin. The above biomass materials have a small number of heteroatoms (atoms other than O and H), a high carbon element content, and a low price, which can avoid the influence of heteroatoms on the hard carbon production process. In addition, the above biomass materials can be crosslinked at a low temperature, which is favorable for forming a more stable skeleton structure, thereby obtaining hard carbon with a suitable channel structure.

[0115] In the present application, the biomass material may be commercially available or may be obtained by extraction from plants.

[0116] In some embodiments, the method for producing hard carbon includes the steps of providing a biomass material, preferably starch, as a carbon source; heat-treating the carbon source in an inert atmosphere at a temperature of 300°C or less for 4 to 60 hours to obtain a first intermediate product; heat-treating the first intermediate product in an air atmosphere at a temperature less than 400°C for 1 to 12 hours to obtain a second intermediate product; and carbonizing the second intermediate product in an inert atmosphere at a temperature of 1000°C to 1600°C for 1 to 12 hours to obtain hard carbon.

[0117] In some embodiments, the method for producing hard carbon includes the steps of providing a biomass material, preferably starch, as a carbon source; heat-treating the carbon source in an inert atmosphere at a temperature of 300°C or less for 4h to 60h to obtain a first intermediate product; heat-treating the first intermediate product in an air atmosphere at a temperature less than 400°C for 1h to 12h to obtain a second intermediate product; pulverizing the second intermediate product to a volume particle size Dv50 of 2μm-15μm and / or Dv90 of 5μm-25μm, and carbonizing the second intermediate product in an inert atmosphere at a temperature of 1000°C to 1600°C for 1h to 12h to obtain hard carbon. secondary battery

[0118] A third aspect of the present embodiment provides a secondary battery. The present application is not particularly limited in the type of the secondary battery, and for example, the secondary battery may be a lithium ion battery, a sodium ion battery, etc., and in particular, the secondary battery is a sodium ion secondary battery. In general, the secondary battery includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. During the charge and discharge process of the secondary battery, active ions are inserted and removed by reciprocating between the positive electrode sheet and the negative electrode sheet, and the electrolyte serves to conduct the active ions between the positive electrode sheet and the negative electrode sheet. [Negative electrode sheet]

[0119] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is provided on one or both of the two opposing surfaces of the negative electrode current collector.

[0120] In some embodiments, the negative electrode film layer comprises at least one of the hard carbon described in any of the embodiments in the first aspect of the present application, and the hard carbon produced by the method described in any of the embodiments in the second aspect of the present application.

[0121] In some embodiments, the negative electrode film layer may further include other negative electrode active materials other than the hard carbon. In some embodiments, the other negative electrode active materials may include, but are not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based materials may include at least one of silicon elemental, silicon oxide, silicon carbon composite, silicon nitrogen composite, and silicon alloy materials. The tin-based materials may include at least one of tin elemental, tin oxide, and tin alloy materials. The present application is not limited to these materials, and other known materials that can be used as negative electrode active materials for secondary batteries may be used.

[0122] In some embodiments, the negative electrode film layer preferably further comprises a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent, and for example, the negative electrode conductive agent may comprise at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≦5% with respect to the total mass of the negative electrode film layer.

[0123] In some embodiments, the negative electrode film layer preferably further includes a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder, and for example, the negative electrode binder can include at least one of styrene butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is ≦5% relative to the total mass of the negative electrode film layer.

[0124] In some embodiments, the negative electrode film layer preferably further comprises other additives. For example, the other additives may comprise a thickener, such as sodium carboxymethylcellulose (CMC-Na), a PTC thermistor material, etc. In some embodiments, the mass percentage of the other additives is ≦2% based on the total mass of the negative electrode film layer.

[0125] In some embodiments, the negative electrode current collector can be a metal foil or a composite current collector. The metal foil can be, for example, a copper foil. The composite current collector can include a polymer substrate layer and a metal material layer formed on at least one surface of the polymer substrate layer. For example, the metal material can be selected from at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer substrate layer can be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0126] The negative electrode film layer is generally formed by applying a negative electrode paste to a negative electrode current collector, drying, and cold pressing. The negative electrode paste is generally formed by dispersing a negative electrode active material, preferably a conductive agent, a binder, and other optional auxiliary agents in a solvent, and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0127] The negative electrode sheet does not exclude additional functional layers other than the negative electrode film layer. For example, in some embodiments, the negative electrode sheet described herein further includes a conductive primer layer (e.g., made of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and provided on the surface of the negative electrode collector. In other embodiments, the negative electrode sheet described herein further includes a protective layer covering the surface of the negative electrode film layer. [Positive electrode sheet]

[0128] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and the positive electrode film layer is provided on one or both of the two opposing surfaces of the positive electrode current collector.

[0129] The positive electrode current collector can be a metal foil or a composite current collector. The metal foil can be, for example, an aluminum foil. The composite current collector can include a polymer substrate layer and a metal material layer formed on at least one surface of the polymer substrate layer. For example, the metal material can be selected from one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer substrate layer can be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0130] The positive electrode film layer generally includes a positive electrode active material, preferably a binder, and preferably a conductive agent. The positive electrode film layer is generally formed by applying a positive electrode paste to the positive electrode current collector, drying, and cold pressing. The positive electrode paste is generally formed by dispersing the positive electrode active material, preferably a conductive agent, a binder, and other optional components in a solvent and stirring uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP). For example, the binder used in the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. By way of example, conductive agents used in the positive electrode film layer include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0131] As the positive electrode active material, a positive electrode active material for secondary batteries known in the art can be used.

[0132] When the secondary battery of the present application is a lithium ion battery, the positive electrode active material can include one or more of a lithium transition metal oxide, a lithium-containing phosphate having an olivine structure, and modified compounds thereof. Examples of the lithium transition metal oxide can include, but are not limited to, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and one or more of their modified compounds. Examples of the lithium-containing phosphate having an olivine structure can include, but are not limited to, lithium iron phosphate, a composite of lithium iron phosphate and carbon, lithium manganese phosphate, a composite of lithium manganese phosphate and carbon, lithium ferromanganese phosphate, a composite of lithium ferromanganese phosphate and carbon, and one or more of their modified compounds. The present application is not limited to these materials, and other known materials that can be used as the positive electrode active material of a lithium ion battery can be used. These positive electrode active materials may be used alone, or two or more of them may be used in combination.

[0133] In some embodiments, in order to further increase the energy density of the secondary battery, the positive electrode active material used in the lithium ion battery can include one or more of the lithium transition metal oxide represented by formula (1) and its modified compounds, Li a Ni b Co c M d O e A f (1) In formula 1, 0.8 ≦ a ≦ 1.2, 0.5 ≦ b < 1, 0 < c < 1, 0 < d < 1, 1 ≦ e ≦ 2, 0 ≦ f ≦ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, B, and A is selected from one or more of N, F, S, Cl.

[0134] For example, the positive electrode active materials used in lithium ion batteries are LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 It may include one or more of O2, LiFePO4, and LiMnPO4.

[0135] When the secondary battery of the present application is a sodium ion battery, and particularly when the secondary battery is a sodium ion secondary battery, the positive electrode active material may include one or more of a sodium-containing transition metal oxide, a polyanion material (e.g., phosphate, fluorophosphate, pyrophosphate, sulfate, etc.), and a Prussian blue-based material. The present application is not limited to these materials, and other known materials that can be used as positive electrode active materials for sodium ion batteries may be used. These positive electrode active materials may be used alone or in combination of two or more.

[0136] For example, the positive electrode active materials used in sodium ion batteries are NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2, Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue-based materials, general formula A a M b (PO4)c O x Y 3-x The material of (A is H + 、Li + 、Na + 、K +、 NH4 + selected from one or more of them, M is a transition metal cation, preferably one or more of V, Ti, Mn, Fe, Co, Ni, Cu, Zn, Y is a halogen anion, preferably one or more of F, Cl, Br, 0 < a ≤ 4, 0 < b ≤ 2, 1 ≤ c ≤ 3, 0 ≤ x ≤ 2), and one or more of them can be included.

[0137] In the present application, the modified compound of each of the above positive electrode active materials can be subjected to doping modification or surface coating modification with respect to the positive electrode active material.

[0138] The positive electrode sheet of the present application does not exclude other additional functional layers other than the positive electrode film layer. For example, in some embodiments, the positive electrode sheet of the present application is sandwiched between the positive electrode current collector and the positive electrode film layer, and further includes a conductive primer layer (for example, composed of a conductive agent and a binder) provided on the surface of the positive electrode current collector. In some other embodiments, the positive electrode sheet of the present application further includes a protective layer that covers the surface of the positive electrode film layer. [Electrolyte]

[0139] The present application does not particularly limit the type of the electrolyte, and it can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolytic solution).

[0140] In some embodiments, the electrolyte uses an electrolytic solution. The electrolytic solution contains an electrolyte salt and a solvent.

[0141] The type of the electrolyte salt is not specifically limited and can be selected according to actual needs.

[0142] When the secondary battery of the present application is a lithium ion battery, for example, the electrolyte salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonylimide (LiFSI), lithium bistrifluoromethanesulfonylimide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium bisoxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium bis(oxalato)difluorophosphanite (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0143] When the secondary battery of the present application is a sodium ion secondary battery, and particularly when it is a sodium ion secondary battery, the electrolyte salt may include one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bisfluorosulfonylimide (NaFSI), sodium bistrifluoromethanesulfonylimide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalate borate (NaDFOB), sodium bisoxalate borate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalato)phosphate (NaDFOP), and sodium tetrafluorooxalate phosphate (NaTFOP).

[0144] The type of the solvent is not particularly limited and can be selected according to actual needs. In some embodiments, by way of example, the solvent may include one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), methylsulfonylmethane (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).

[0145] In some embodiments, the electrolyte preferably further includes an additive, for example, the additive may include an anode film-forming additive, may include a cathode film-forming additive, and may further include an additive that can improve a specific performance of the battery, such as an additive that improves the overcharge characteristics of the battery, an additive that improves the high temperature characteristics of the battery, an additive that improves the low temperature output characteristics of the battery, etc. [Separator]

[0146] The secondary battery using an electrolyte or a secondary battery using a solid electrolyte further includes a separator. The separator is disposed between the positive electrode sheet and the negative electrode sheet and serves to isolate the positive electrode sheet. The present application does not particularly limit the type of the separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.

[0147] In some embodiments, the separator may be made of one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a monolayer film or a multilayer composite film. When the separator is a multilayer composite film, the materials of each layer may be the same or different.

[0148] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be wound or laminated to produce an electrode assembly.

[0149] In some embodiments, the secondary battery may include an exterior material, which is used to encapsulate the electrode assembly and the electrolyte.

[0150] In some embodiments, the secondary battery's exterior material may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The secondary battery's exterior material may be a soft pack, such as a pouch-type soft pack, etc. The material of the soft pack may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0151] The present application does not particularly limit the shape of the secondary battery, and the secondary battery may be cylindrical, rectangular, or any other shape. Fig. 2 shows a secondary battery 5 having a rectangular structure as an example.

[0152] In some embodiments, as shown in FIG. 3, the exterior material may include a housing 51 and a cover plate 53. The housing 51 includes a bottom plate and a side plate connected to the bottom plate. A receiving cavity is formed by being surrounded by the bottom plate and the side plate. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening and seal the receiving cavity. The electrode assembly 52 may be formed from a positive electrode sheet, a negative electrode sheet and a separator through a winding process or a lamination process. The electrode assembly 52 is sealed in the receiving cavity. An electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be adjusted as needed.

[0153] The method for manufacturing the secondary battery of the present application is well known. In some embodiments, a secondary battery can be formed by assembling a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. For example, an electrode assembly can be formed from a positive electrode sheet, a separator, and a negative electrode sheet through a winding process or a lamination process, and the electrode assembly can be placed in an exterior material, dried, and then an electrolyte can be injected, and a secondary battery can be obtained through processes such as vacuum sealing, standing, precharging, and shaping.

[0154] In some embodiments of the present application, the secondary battery according to the present application can be assembled into a battery module, and the number of secondary batteries included in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0155] Fig. 4 is a schematic diagram of an example battery module 4. As shown in Fig. 4, in the battery module 4, a plurality of secondary batteries 5 can be arranged in sequence along the length direction of the battery module 4. Of course, any other arrangement may be used. The plurality of secondary batteries 5 can be fixed by fasteners.

[0156] Preferably, the battery module 4 may further include an outer case having an accommodation space in which the plurality of secondary batteries 5 are accommodated.

[0157] In some embodiments, the above battery modules can be further assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0158] 5 and 6 are schematic diagrams of an example battery pack 1. As shown in Fig. 5 and 6, the battery pack 1 may include a battery case and a plurality of battery modules 4 installed in the battery case. The battery case includes an upper housing 2 and a lower housing 3, and the upper housing 2 is used to cover the lower housing 3 and form a sealed space that houses the battery modules 4. The plurality of battery modules 4 may be arranged in the battery case in any manner. power consumption equipment

[0159] An embodiment of the present application further provides a power consuming device including at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack may be used as a power source of the power consuming device, or may be used as an energy storage element of the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a train, a ship, a satellite, an energy storage system, etc.

[0160] The power consumption device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0161] 7 is a schematic diagram of an example power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or battery module can be used to meet the high power and high energy density requirements of the power consuming device.

[0162] Other examples of power consuming devices include mobile phones, tablet computers, notebook computers, etc. Such power consuming devices are generally required to be lightweight and thin, and can use secondary batteries as a power source. Working Example

[0163] The following examples more specifically describe the contents disclosed in the present application, but since various modifications and changes made within the scope of the contents disclosed in the present application are obvious to those skilled in the art, these examples are merely illustrative.Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without treatment, and all equipment used in the examples are commercially available. Example 1

[0164] The corn starch used as the carbon source is placed in a tubular furnace, heated to 300°C (first temperature t1) at 5°C / min under a nitrogen gas atmosphere, and then heat-treated at a constant temperature for 18 hours (heat treatment time t1) to obtain a first intermediate product. The nitrogen gas atmosphere is changed to an air atmosphere, and the temperature is then raised to 300°C (second temperature T2) at 3°C / min, and then heat-treated at a constant temperature for 2 hours (heat treatment time T2) to obtain a second intermediate product. The obtained second intermediate product is crushed until the volume particle size Dv50 is 4μm to 8μm and the Dv90 is 8μm to 15μm, and then heated to 1100°C (third temperature T3) at 5°C / min under a nitrogen gas atmosphere, and then heat-treated at a constant temperature for 12 hours (heat treatment time T3) to obtain hard carbon. Examples 2 to 20

[0165] The method for producing hard carbon was the same as in Example 1, except that the manufacturing process parameters for hard carbon were adjusted, as shown in Table 1. Comparative Example 1

[0166] The corn starch used as the carbon source is placed in a tubular furnace, heated to 240°C at 3°C / min under a nitrogen gas atmosphere, and then heat-treated at the same temperature for 36 hours to obtain a first intermediate product. The first intermediate product obtained is pulverized to a volume particle size Dv50 of 4μm to 8μm and Dv90 of 8μm to 15μm, and then heated to 1200°C at 5°C / min under a nitrogen gas atmosphere, and then heat-treated at the same temperature for 12 hours to obtain hard carbon. Comparative Example 2

[0167] The corn starch used as the carbon source is placed in a tubular furnace, heated to 240°C at 3°C / min in an air atmosphere, and then heat-treated at the same temperature for 36 hours to obtain a first intermediate product. The first intermediate product obtained is pulverized to a volume particle size Dv50 of 4μm to 8μm and Dv90 of 8μm to 15μm, and then heated to 1200°C at 5°C / min in a nitrogen gas atmosphere, and then heat-treated at the same temperature for 12 hours to obtain hard carbon. Comparative Example 3

[0168] The corn starch used as the carbon source is placed in a tubular furnace, heated to 300°C at 3°C / min in an air atmosphere, and then heat-treated at the same temperature for 2 hours to obtain a first intermediate product. The first intermediate product obtained is pulverized to a volume particle size Dv50 of 4μm to 8μm and Dv90 of 8μm to 15μm, and then heated to 1200°C at 5°C / min in a nitrogen gas atmosphere, and then heat-treated at the same temperature for 12 hours to obtain hard carbon. Comparative Examples 4 to 6

[0169] The method for producing hard carbon was the same as in Example 1, except that the manufacturing process parameters for hard carbon were adjusted, as shown in Table 1.

[0170] The hard carbon and binder styrene butadiene rubber (SBR), thickener sodium carboxymethylcellulose (CMC-Na), and conductive carbon black prepared in each Example and Comparative Example are thoroughly stirred and mixed in an appropriate amount of solvent deionized water in a mass ratio of 96.2:1.8:1.2:0.8 to form a uniform negative electrode paste. The negative electrode paste is uniformly applied to the surface of the copper foil of the negative electrode current collector, dried in an oven, and then prepared for use. Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and NaPF6 is dissolved in the organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L. Then, a CR2430 button battery is assembled in an argon-protected glove box using a metallic sodium sheet as a counter electrode and a polyethylene (PE) film as a separator.

[0171] At 25°C, the button batteries manufactured in each Example and Comparative Example were first discharged at a constant current of 10 mA / g to 0 V, and the first cycle discharge capacity of the button batteries was recorded. Then, the button batteries were charged at a constant current of 10 mA / g to 2.0 V, and the first cycle charge capacity of the button batteries was recorded.

[0172] Specific capacity of hard carbon (mAh / g) = first cycle charge capacity of button cell / mass of hard carbon.

[0173] Initial coulombic efficiency of hard carbon (%) = first cycle charge capacity of button cell / first cycle discharge capacity of button cell × 100%.

[0174] The test results of Examples 1 to 20 and Comparative Examples 1 to 6 are shown in Table 2.

[0175] FIG. 8 is a scanning electron microscope (SEM) photograph of the hard carbon produced in Example 2. As can be seen from FIG. 8, the hard carbon obtained by the production method of the present application has a regular morphology and a uniform size.

[0176] 9 and 10 are nitrogen adsorption isotherms measured at a temperature of 77K for the hard carbons produced in Example 2 and Comparative Example 1, respectively.

[0177] As shown in FIG. 9, the nitrogen adsorption isotherm measured at a temperature of 77 K for the hard carbon produced in Example 2 satisfies the requirements for the type I adsorption isotherm in FIG. 1, and the nitrogen relative pressure P / P0 is 10 -8 The total amount of nitrogen adsorption between 0.035 and 0.117.1 cm 3 (STP) / g, and the total nitrogen adsorption amount between the nitrogen relative pressure P / P0 of 0.035 and 1 is 15.5 cm 3 (STP) / g, and meets the requirement of V2 / V1≦0.20. As can be seen from the test results in Table 2, the specific capacity of the hard carbon prepared in Example 2 is 403mAh / g, and the initial Coulombic efficiency is 85.4%. Although the mechanism is not yet clear, the inventors speculate that one possible reason is that the channel structure of the hard carbon prepared in Example 2 is appropriate and developed, and the hard carbon can provide many active ion storage sites, so that the specific capacity is high; at the same time, the channel structure of the hard carbon is developed, and the active ions stored in the active ion storage sites are easily desorbed, so that the initial Coulombic efficiency of the hard carbon is also high.

[0178] In Comparative Example 1, corn starch was subjected to a low-temperature heat treatment process in an inert atmosphere, and then directly subjected to a high-temperature carbonization process in an inert atmosphere. As shown in FIG. 10, the nitrogen adsorption isotherm measured at a temperature of 77K of the hard carbon produced in Comparative Example 1 does not meet the requirements of the type I adsorption isotherm of FIG. 1, but is similar to the type II adsorption isotherm of FIG. 1, and the nitrogen adsorption isotherm measured at a temperature of 77K of the hard carbon produced also does not meet the requirements of V2 / V1≦0.20 and 20≦V1≦150. As can be seen from the test results in Table 2, the specific capacity of the hard carbon produced in Comparative Example 1 is only 251mAh / g, and the initial coulombic efficiency is only 77.7%. The possible reason is that the hard carbon produced in Comparative Example 1 has a small micropore structure, which cannot provide many active ion storage sites, and the utilization rate of the few active ion storage sites it has is also low. In addition, the proportion of large pores (e.g., mesopores or macropores) in the hard carbon prepared in Comparative Example 1 was too high, so that even if the hard carbon was used for a secondary battery, the proportion of electrolyte infiltrated areas inside the hard carbon was too high, which further reduced the utilization rate of the active ion storage sites.

[0179] In Comparative Example 2 and Comparative Example 3, corn starch was subjected to a low-temperature heat treatment process in an air atmosphere, and then directly subjected to a high-temperature carbonization process in an inert atmosphere, but the hard carbon produced does not have both a high specific capacity and a high initial coulombic efficiency. The possible reason is that the hard carbon produced in Comparative Example 2 and Comparative Example 3 also has a small micropore structure, so it cannot provide many active ion storage sites, and the utilization rate of the few active ion storage sites that it does have is also low. In addition, the proportion of large pores in the hard carbon produced in Comparative Example 2 and Comparative Example 3 is too high, so even if the hard carbon is produced into a secondary battery, the proportion of the electrolyte infiltrated area inside the hard carbon is too high, which further reduces the utilization rate of the active ion storage sites.

[0180] In Comparative Examples 4 to 6, corn starch was subjected to a low-temperature heat treatment process in an inert atmosphere, a secondary low-temperature heat treatment process in an air atmosphere, and a high-temperature carbonization process in an inert atmosphere simultaneously. However, the heat treatment temperature and heat treatment time were not reasonable, and none of the adsorption isotherms of the produced hard carbons could simultaneously meet the requirements of V2 / V1≦0.20 and 20≦V1≦150. None of the produced hard carbons had both high specific capacity and high initial coulombic efficiency.

[0181] In Comparative Example 4, the heat treatment time in the air during the preparation of the hard carbon was too long, which resulted in excessive formation of pores in the hard carbon, the channel structure of the hard carbon being destroyed, and the pores were easily merged, increasing the number and ratio of large pores inside the hard carbon. Even if the hard carbon is used for a secondary battery, the ratio of the electrolyte infiltrated area inside the hard carbon increases, decreasing the utilization rate of the active ion storage site, making it difficult for the hard carbon to have both high specific capacity and high initial coulombic efficiency.

[0182] In Comparative Example 5, the third temperature T3 is too low when producing hard carbon, so that the produced hard carbon contains a large amount of extremely fine pore structures, and these extremely fine pore structures have low strength and are easily destroyed or collapsed, resulting in pore merging, and the number and proportion of large pores inside the hard carbon are both increased. Even if the hard carbon is produced into a secondary battery, the proportion of the electrolyte infiltrated area inside the hard carbon increases, and the utilization rate of the active ion storage site decreases, making it difficult for the hard carbon to have a high specific capacity and a high initial Coulombic efficiency.

[0183] In Comparative Example 6, the third temperature T3 is too high when producing the hard carbon, which makes it easy for microscopic movement to occur in the graphite microcrystal structure formed in the carbonization process, and the channel structure of the hard carbon is forcibly adjusted and the number of the channel structures is greatly reduced, making it difficult for the hard carbon to have both high specific capacity and high initial Coulombic efficiency.

[0184] The test results of Examples 1 to 20 show that when the nitrogen adsorption isotherm of the hard carbon measured at a temperature of 77K simultaneously satisfies the requirements of V2 / V1≦0.20 and 20≦V1≦150, the hard carbon has both high capacity and initial coulombic efficiency. The test results of Examples 1 to 20 further show that when the nitrogen adsorption isotherm of the hard carbon measured at a temperature of 77K further satisfies the requirements of 0.08≦V2 / V1≦0.20, 70≦V1≦150, and 6≦V2≦30, the capacity and initial coulombic efficiency of the hard carbon are further improved.

[0185] The present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment that has substantially the same configuration as the technical idea and exhibits the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can conceive of are added to the embodiment, and other forms constructed by combining some of the components in the embodiment are also included in the scope of the present application, as long as they do not deviate from the gist of the present application.

[0186] [Table 1]

[0187] [Table 2]

Claims

1. In the nitrogen adsorption isotherm measured at a temperature of 77 K, the nitrogen relative pressure P / P 0 is 10 -8 The total amount of nitrogen adsorption between V and 0.035 1 cm 3 (STP) / g, and nitrogen relative pressure P / P 0 The total amount of nitrogen adsorption between 0.035 and 1 is V 2 cm 3 (STP) / g, 0.119≦V 2 / V 1 ≦0.20 and 92.5≦V 1 ≦150, where P is the absolute pressure of nitrogen, and P 0 represents the saturated vapor pressure of nitrogen at a temperature of 77 K.

2. 98.5≦V 1 2. The hard carbon according to claim 1, wherein the hard carbon has a molecular weight of ≦150.

3. 101.6≦V 1 3. The hard carbon according to claim 2, wherein the molecular weight is ≦150.

4. 0.132≦V 2 / V 1 The hard carbon according to any one of claims 1 to 3, wherein the hard carbon has a molecular weight of ≦0.

20.

5. 0.154≦V 2 / V 1 5. The hard carbon according to claim 4, wherein the ratio is ≦0.

20.

6. 12.5≦V 2 The hard carbon according to any one of claims 1 to 5, wherein the hard carbon has a molecular weight of ≦30.

7. 15.5≦V 2 7. The hard carbon according to claim 6, wherein the molecular weight is ≦30.

8. In the Raman spectrum, I d / I g is 1.20 to 1.32, and I d is 1350±50cm -1 represents the d-band peak intensity in the Raman shift range of g is 1580±50cm -1The hard carbon according to claim 1 , wherein the g-band peak intensity is in a Raman shift range of 0.1 to 0.

5.

9. The hard carbon according to any one of claims 1 to 8, wherein in an X-ray diffraction spectrum, the 2θ value corresponding to the 002 peak is between 22° and 24°.

10. The volume particle diameter Dv50 is 2 μm to 15 μm. The volume particle diameter Dv90 is 5 μm to 25 μm. The specific surface area is 5 m 2 / g or less; and The green density at a force of 50,000 N is 0.96 g / cm 3 ~1.05g / cm 3 Condition (4) The tap density is 0.80 g / cm 3 ~0.95g / cm 3 The hard carbon according to any one of claims 1 to 9, which satisfies at least one of the following conditions:

11. Condition (1) that the volume particle diameter Dv50 is 4 μm to 8 μm; The volume particle diameter Dv90 is 8 μm to 15 μm. The specific surface area is 0.5 m 2 / g to 5m 2 The hard carbon according to claim 10, which satisfies at least one of the following conditions:

12. A step S10 of providing a carbon source; Step S20: heat-treating the carbon source in an inert atmosphere at a first temperature T1 for t1 hours to obtain a first intermediate product, where T1≦300° C. and t1 is 4 h to 60 h; Step S30 of heat-treating the obtained first intermediate product in an air atmosphere at a second temperature T2 for a time t2 to obtain a second intermediate product, where T2<400° C. and t2 is 1 h to 12 h; A step S40 of carbonizing the obtained second intermediate product in an inert atmosphere at a third temperature T3 for t3 hours to obtain hard carbon, where T3 is 1000° C. to 1600° C. and t3 is 1 h to 12 h; Including, The hard carbon has a nitrogen adsorption isotherm measured at a temperature of 77 K, and the nitrogen relative pressure P / P 0 is 10 -8 The total amount of nitrogen adsorption between V and 0.035 1 cm 3 (STP) / g, and nitrogen relative pressure P / P 0 The total amount of nitrogen adsorption is between 0.035 and 1 V 2 cm 3 (STP) / g, 0.119≦V 2 / V 1 ≦0.20 and 92.5≦V 1 ≦150, where P is the absolute pressure of nitrogen, and P 0 A method for producing hard carbon, where the saturated vapor pressure of nitrogen at a temperature of 77K is shown.

13. 13. The method of claim 12, wherein T1≦T2.

14. T1 is between 180°C and 300°C, and / or T2 is between 270°C and 380°C, and / or The method according to claim 12 or 13, wherein T3 is between 1000°C and 1400°C.

15. Step (a), which further includes a step S21, after step S20 and before step S30, of crushing the first intermediate product obtained in step S20; Step (b), which further includes, after step S30 and before step S40, a step S31 of crushing the second intermediate product obtained in step S30; and (c) a step S50 of crushing the hard carbon obtained in step S40.

16. 16. The method of claim 15, wherein in step (b), the volume particle size of the second intermediate product after crushing satisfies the requirement that Dv50 is 2 μm to 15 μm and / or Dv90 is 5 μm to 25 μm.

17. 17. The method of any one of claims 12 to 16, wherein the inert atmosphere is selected from one or more of a nitrogen gas atmosphere, an argon gas atmosphere.

18. 18. The method of any one of claims 12 to 17, wherein the carbon source comprises one or more of a polymer, a resin, and a biomass material.

19. The polymer comprises one or more of polyaniline, polypyrrole, and / or The resin comprises one or more of a phenolic resin, an epoxy resin, and / or 20. The method of claim 18, wherein the biomass material comprises one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, and lignin.

20. A secondary battery comprising a negative electrode sheet comprising the hard carbon according to claim 1 .

21. 21. A power consuming device comprising the secondary battery of claim 20.

Citation Information

Patent Citations

  • Hard carbon material and preparing method and application thereof

    CN108584907A

  • Method for preparing hard carbon negative electrode material and high-specific-capacity lithium ion battery by taking rose willow as carbon source

    CN112811409A

  • Nanocarbon material composite biomass hard carbon electrode material and preparation method and application thereof

    CN113044827A

  • Boron-doped activated carbon material

    JP2018514936A

  • Biological material-derived hard carbon, negative electrode material, negative electrode, and alkali ion battery

    JP2021066629A